2016
DOI: 10.1007/s10826-016-0564-9
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Positive Parenting Programme on a Mother and Baby Unit: Q-Methodology with Staff

Abstract: The Baby Triple P Positive Parenting Programme, a new addition to the established Triple P programmes, is currently being considered for a trial in a Mother and Baby Unit with the aim of exploring its benefits to mothers presenting with severe mental illness. The aim of the current study was to investigate staff views of the acceptability and feasibility of a parenting programme such as the Baby Triple P Positive Parenting Programme in a Mother and Baby Unit. Q-methodology, using an 88-item Q-sort, was employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It could be hypothesised that the parenting support and interventions received during co-admission to an MBU could help to foster more positive mother-baby attachments [31] – perhaps by improving maternal sensitivity, a key theoretical aspect of parenting related to attachment [32, 33]. More research is needed to explore this, since national guidance on parenting interventions in MBUs is currently limited [34, 35], due to a lack of evidence for the effectiveness of parenting interventions for women experiencing severe mental illness, especially in MBU settings [36].…”
Section: Discussionmentioning
confidence: 99%
“…It could be hypothesised that the parenting support and interventions received during co-admission to an MBU could help to foster more positive mother-baby attachments [31] – perhaps by improving maternal sensitivity, a key theoretical aspect of parenting related to attachment [32, 33]. More research is needed to explore this, since national guidance on parenting interventions in MBUs is currently limited [34, 35], due to a lack of evidence for the effectiveness of parenting interventions for women experiencing severe mental illness, especially in MBU settings [36].…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the feasibility and acceptability of parenting interventions in SMI have yielded promising results (Butler, Hare, Walker, Wieck, & Wittkowski, 2014; Butler‐Coyne, Hare, Walker, Wieck, & Wittkowski, 2017; Jones et al ., 2015). Furthermore, research into the impact of a self‐directed parenting intervention involving children and parents with psychosis (Wolfenden et al , (unpublished doctoral thesis)) indicated positive effects on parental mental health as well as child behaviour.…”
mentioning
confidence: 99%
“…We conducted two studies to investigate patient ( n = 15) and staff ( n = 16) views and opinions regarding the acceptability of an intervention like Baby Triple P being offered on a MBU [ 45 , 46 ]. These findings alongside information from a pilot study of Baby Triple P offered to mothers with postnatal depression [ 44 ] and patient and public involvement consultations were used to inform the treatment and implementation protocol of this RCT.…”
Section: Methodsmentioning
confidence: 99%
“…However, without staff support, the possible implementation of this intervention on the MBU would be difficult. Consequently, we conducted another study with MBU staff [ 46 ], which showed that staff also regarded this intervention to be feasible and acceptable for the MBU setting. MBU staff indicated that the intervention could help reduce the ‘bad parent’ stigma often identified in the population of mothers presenting with severe mental health difficulties [ 35 ].…”
Section: Introductionmentioning
confidence: 99%